Cryofibrinogenaemia: not just skin deep. (20th February 2013) - Sandouk, Zahrae; Alirhayim, Zaid; Hassan, Syed; Qureshi, Waqas
Abstract : A Caucasian woman in her 60s with a history of rheumatoid arthritis presented to our institution complaining of skin ulceration. Her initial course was complicated by superinfection and sepsis until a diagnosis of cryofibrinogenaemia was finally established. Cryofibrinogenaemia remains as an under-recognised entity in part, because it can mimic other causes of skin ulcerations. In addition, its diagnosis can be challenging because of the particular handling techniques required of lab specimens. This case exemplifies some of the diagnostic and treatment challenges encountered while managing the patient with cryofibrinogenaemia.